한국과 중국 대학생의 e-헬스 리터러시, 건강정보 신뢰도 및 건강행위가 건강정보 이용 동기에 미치는 영향 비교연구 - 남영희(Young Hee Nam); 정인숙(In Suk Jung) (디지털콘텐츠학회논문지, 2020)
본 연구는 한국 대학생과 중국 유학생의 e-헬스 리터러시, 건강정보 신뢰도 및 건강행위가 건강정보 이용 동기에 미치는 영향을 비교하기 위하여 수행되었다. 연구대상자는 C시에 소재한 일개 대학의 재학생 중 한국과 중국 학생 240명 이었다. 자료분석은 SPSS/WIN 23.0 program을 이용하여 통계처리 하였다. 연구결과는 첫째, 건강관심도에서 한국 학생은 e-헬스 리터러시(F=8.202, p<.001)와 건강정보 신뢰도(F=7.434, p=.001)에서 유의하였고, 중국 학생은 e-헬스 리터러시(F=13.073, p<.001), 건강정보 신뢰도(F=11.736, p<.001), 건강행위(F=3.612, p=.030)에서 유의하였다. 둘째, 건강정보 이용 동기에 영향 요인은 두 집단 모두 e-헬스 리터러시(t=2.567, p=.012, t=2.834, p=.005)와 건강정보 신뢰도(t=3.861, p<.001, t=3.930, p<.001)로 나타났다. 따라서 e-헬스 리터러시, 건강정보 신뢰도를 높이려면 건강 행위를 지속적으로 수행하려는 노력과 정확한 건강정보를 획득하기 위한 혜안이 요구된다. This study was to compare the effects of e-health literacy, reliability of health information and health behavior on motivation to use health information in Korean and Chinese university students. The subjects of this study were 240 Korean and Chinese students attending a university in C city. Data analysis was performed by using SPSS / WIN 23.0 program. The results of the study were as follows: 1. In health interest, Korean students were significantly associated with e-health literacy (F=8.202, p<.001) and health information reliability (F=7.434, p=.001), while Chinese students were significantly associated with e-health literacy (F=13.073, p<.001), health information reliability (F=11.736, p<.001), Health behavior (F=3.612, p=.030). 2. The factors affecting the motivation of using health information were e-health literacy (t=2.567, p=.012, t=2.834, p=.005) and reliability of health information (t=3.861, p<.001, t=3.930, p<.001). Therefore, to increase of e-health literacy and health information reliability, efforts to continuously perform health behaviors and obtain accurate health information are required. KCI Citation Count: 8